The learning environment as a predictor of higher order thinking skills - Mohd Saifulkhair Omar; Mohd Isha Awang (International Journal of Evaluation and Research in Education (IJERE), 2023)
The learning environment is one of the elements that will influence higher-order thinking skills (HOTS). The purpose of this study was to test the influence of the learning environment on HOTS. The researcher selected 82 forms two students from two secondary schools in Kuala Nerus, Terengganu, Malaysia, as the study sample. The researcher has adopted a set of questionnaires that have been developed by previous researchers and a questionnaire developed by the researcher himself. Multiple regression analysis has found that material environment and cooperation between students’ constructs are predictors of HOTS. Therefore, the Ministry of Education Malaysia as a stakeholder in the education sector in the country is expected to: i) Allocate ample expenditure to purchase and maintain all laboratory equipment and materials and ii) Organize workshops on the maintenance of laboratory equipment and materials for laboratory assistants in high school to ensure they are always in the best possible condition. The researcher suggested that future studies focus on producing maintenance modules for the materials and science equipment for laboratory assistants’ use. It is hoped that with this module, the focus on improving Malaysian students’ HOTS will be easily achieved by 2025.